2019
DOI: 10.1101/665281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A systems chemoproteomic analysis of acyl-CoA/protein interaction networks

Abstract: CoA metabolite interactions, enabling the identification of biological processes susceptible to altered acetyl-CoA levels. Finally, we utilize systems-level analyses to assess the features of novel protein networks that may interact with acyl-CoAs and demonstrate a strategy for high-confidence annotation of direct acetyl-CoA binding proteins and AT enzymes in human proteomes. Overall our studies illustrate the power of integrating chemoproteomics and systems biology analysis methods and provide a novel resourc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…9−12 Recently, in the process of characterizing a histone acetyltransferase chemoproteomic probe, we discovered that CoA-based affinity resins exhibit broad-spectrum capture properties, enriching lysine acetyltransferases, N-terminal and metabolic acetyltransferases, and several CoA and NAD-based metabolic enzymes (e.g., oxidoreductases). 13,14 This indicates that CoA-based chemoproteomic probes may have utility in studying the pharmacological interactions of additional enzyme classes, beyond histone acetyltransferases. However, one challenge in applying this approach is how to differentiate a "true hit" from the background.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9−12 Recently, in the process of characterizing a histone acetyltransferase chemoproteomic probe, we discovered that CoA-based affinity resins exhibit broad-spectrum capture properties, enriching lysine acetyltransferases, N-terminal and metabolic acetyltransferases, and several CoA and NAD-based metabolic enzymes (e.g., oxidoreductases). 13,14 This indicates that CoA-based chemoproteomic probes may have utility in studying the pharmacological interactions of additional enzyme classes, beyond histone acetyltransferases. However, one challenge in applying this approach is how to differentiate a "true hit" from the background.…”
mentioning
confidence: 99%
“…Of note, the use of TMT tagging represents a technical advance over our previous studies, which have demonstrated the utility of label-free spectral counting in analysis of acyl-CoA/protein interactions. 14 Applying our chemoproteomic probes in combination with a 4-plex TMTtagging strategy allowed comparative quantification of proteins enriched from HEK293T proteomes under four affinity capture conditions: (i) probe 1 (no competitor), (ii) probe 2 (no competitor), (iii) probe 1 (0.1 mM acetyl-CoA competitor), and (iv) probe 2 (0.1 mM acetyl-CoA competitor; Figure 2a). Three independent experiments were performed, and individual protein abundances were normal- ized relative to the overall protein intensity quantified in each tagged sample in order to account for any technical variations (i.e., sample loss) introduced prior to TMT tagging.…”
mentioning
confidence: 99%
“…4,5 Acetyl-CoA also plays an important role in epigenetic signaling, protein homeostasis, and protein synthesis due to its ability to serve as a cofactor used in the modifications of proteins [6][7] and RNA. 7 Over the last decade, substantial evidence indicates these processes can be regulated by subcellular acetyl-CoA levels, [8][9][10] highlighting the potential for acetyl-CoA to directly link metabolism and gene expression. Emphasizing this, a recent study demonstrated that concentrations of acetyl-CoA in the nucleus are distinct from those in other organelles.…”
mentioning
confidence: 99%
“…1b). To assess whether this approach could be leveraged for selective sensing, we analyzed a previous chemoproteomic dataset which determined how capture of proteins by a CoA-based affinity resin were competed by acetyl-CoA or CoA, 10 fitting quantitative abundance data to a nonlinear regression model. Since CoA affinity resins can capture both direct and indirect interactors 23 we focused on 23 proteins known to directly bind to acetyl-CoA, 24 13 of which displayed dose-dependent competition (R 2 > 0.85) by both metabolites (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation